Esthesioneuroblastoma: An Update on the Massachusetts Eye and Ear Infirmary and Massachusetts General Hospital Experience with Craniofacial Resection, Proton Beam Radiation, and Chemotherapy - Herr, Marc W.; Sethi, Rosh K. V.; Meier, Joshua C.; Chambers, Kyle J.; Remenschneider, Aaron; Chan, Annie; Curry, William T.; Barker, Fred G., II; Deschler, Daniel G.; Lin, Derrick T. (Journal of Neurological Surgery Part B: Skull Base, 2014)
Objectives To update the Massachusetts General Hospital (MGH) and Massachusetts Eye and Ear Infirmary (MEEI) experience in the management of esthesioneuroblastoma (ENB) with multimodality therapy and to reassess treatment outcomes and complications in a larger cohort with longer follow-up times.Design A retrospective chart review.Setting A tertiary referral center.Participants All patients presenting with ENB and managed at the MGH and MEEI from 1997 to 2013.Main Outcome Measures Disease-free and overall survival.Results Twenty-two patients were identified with an average follow-up of 73 months. Ten patients presented with Kadish stage B disease and 12 with stage C disease. A total of six patients (27%) developed regional metastases. Treatment for all patients included craniofacial resection (CFR) followed by proton beam irradiation with or without chemotherapy. The 5-year disease-free and overall survival rates were 86.4% and 95.2%, respectively, by Kaplan-Meier analysis. Negative margins were a significant factor in disease-free survival. One patient experienced severe late-radiation toxicity.Conclusions ENB is safely and effectively treated with CFR followed by proton beam irradiation. The high incidence of regional metastases warrants strong consideration for elective neck irradiation. Proton beam radiation is associated with lower rates of severe late-radiation toxicity than conventional radiotherapy.
Keywords: esthesioneuroblastoma; craniofacial resection; proton beam radiation; sinonasal malignancy